Analisis Kinerja Dinas Kebudayaan Dan Pariwisata Bengkulu Dalam Pengembangan Objek Wisata Pantai Laguna - Cahyadi Kurniawan (Indonesian Journal Publisher, 2022)
The Bengkulu City, The Tourism and Culture Office is a government entity with the jurisdiction and obligation to administer and manage the tourist and cultural sector to assist regional revenue. The Department of Tourism and Culture is responsible for creating new tourist attractions, which must be maintained. This study aims to analyze and determine the performance of the Tourism Office in developing Laguna Beach Tourism Objects in Bengkulu Province, using four tourism development components: Promotion Tours, Information Services, and Accessibility. The research method uses a qualitative descriptive approach. Data collection techniques are carried out with social media data and news media, which are then captured through the Nvivo 12 Plus feature to capture news mass media content with the keywords Laguna Beach, Twitter social media, and Instagram social media Laguna Beach tourism office related to Tourism Branding Lagoon Beach. The results of the study show tourism development in Laguna Beach. The strategy implemented by the government, such as tourism promotion, is a good step in increasing tourism; as we know, in promoting a tourist spot with social media and mass media, the impact is very effective, as well as for quality and Content-based and international-standard content-based tourism HR professionals need to be further improved so that they can compete with other tourist destinations throughout Indonesia